NGALAP BAR?KAH DAN KAR?MAH (Analisis Makna Ziarah di Makam Mbah Priok, Koja Jakarta Utara) - Moh. Toriqul Chaer (MUADDIB Jurnal Kependidikan dan Keislaman, 2014)
The existence of a holy man, a lover of God, the doctrine of Islam called Wali Allah. Activity pilgrimage to the tomb not only pray, but also to gain supernatural powers of spirits who are in sacred locations. The supernatural aspect is often called barkah and Karmah. This study focuses on the tomb of Mbah Priok, Koja, North Jakarta. Tomb became the object of pilgrimage because they have the blessings and miracles. This study uses an interpretive ethnography, how pilgrims give meaning to the tomb. Results of the study note that the pilgrims who visit the tomb of Mbah Priok, Koja, North Jakarta generally have confidence that Mbah Priok has a big name in the field of religion and meritorious. In addition to the belief in the ability or strength possessed mystical Mbah Priok during his lifetime. In general, the pilgrims visited tomb in an attempt to establish communication with Allah. In addition to efforts to denounce the problems of life, which is dominated by economic issues. There are several pilgrim deliberately pilgrimage to tomb to reach certain spiritual stages. In thiscase the shrine of the tomb, Koja, North Jakarta involves the conception of the trustees as an essential part of determining the blessings and miracles.